La disortografía en la macro destreza de escribir, en los estudiantes del cuarto año de educación general básica de la unidad educativa Nela Martínez Espinosa del cantón la Troncal de la provincia del Cañar en el periodo lectivo 2015 – 2016. - Beltrán Uzhca, Mónica Jhane (2017)
The contents of this thesis are detailed in the following diagram: In Chapter I, the Reference Framework is described with the problem approach, formulation, general objectives, specific, and the research problem is justified. In Chapter II, the theoretical framework is described, with the scientific theories that guide the research work, on the variables that are the Disortography in the macro skill of Writing, the variables are mentioned. Chapter III establishes the Methodological Framework, which describes the methodology of the research, as well as its type, study design, to later establish the population and sample, as well as the techniques and instruments of data collection and finally The techniques of procedures for the analysis of the information resulting from the completed research process. In Chapter IV.- Analysis and Interpretation of results establish the methods that aid the investigation. The techniques of data collection, the same as the survey and observation with their respective instruments. The work was done with all the corresponding population. For the data processing, the percentage method was used to determine the correct percentage of each observed aspect, then an analysis and interpretation of results is made to record the effects of dysortography in children and children, conclusions and recommendations. In Chapter IV.- Describes Effects, Conclusions and Recommendations of the investigative work referring to the disortografía.Es opio to note that this work has a Bibliography and Web graphics with documents that allowed to compile fundamental information for the development of the investigative work. ANNEXES detailed the instruments of data collection as well as the evidences of the investigative work which is demonstrated in the photos of the institution with the children